Effect of Non-thermal Atmospheric Plasma on Viability and Histamine-Producing Activity of Psychotrophic Bacteria in Mackerel Fillets - Trevisani, Marcello; Cevoli, Chiara; Ragni, Luigi; Cecchini, Matilde; Berardinelli, Annachiara (Frontiers in Microbiology, 2021)
Non-thermal atmospheric plasma (NTAP) has gained attention as a decontamination and shelf-life extension technology. In this study its effect on psychrotrophic histamine-producing bacteria (HPB) and histamine formation in fish stored at 0-5°C was evaluated. Mackerel fillets were artificially inoculated with Morganella psychtotolerans and Photobacterium phosphoreum and exposed to NTAP to evaluate its effect on their viability and the histidine decarboxylase activity in broth cultures and the accumulation of histamine in fish samples, stored on melting ice or at fridge temperature (5°C). NTAP treatment was made under wet conditions for 30 min, using a dielectric barrier discharge reactor. The voltage output was characterized by a peak-to-peak value of 13.8 kV (fundamental frequency around 12.7 KHz). This treatment resulted in a significant reduction of the number of M. psychrotolerans and P. phosphoreum (approximately 3 log cfu/cm2) on skin samples that have been prewashed with surfactant (SDS) or SDS and lactic acid. A marked reduction of their histamine-producing potential was also observed in histidine decarboxylase broth incubated at either 20°C or 5°C. Lower accumulation of histamine was observed in NTAP-treated mackerel fillets that have been inoculated with M. psychrotolerans or P. phosphoreum and pre-washed with either normal saline or SDS solution (0.05% w/v) and stored at 5°C for 10 days. Mean histamine level in treated and control groups for the samples inoculated with either M. psychrotolerans or P. phosphoreum (approximately 5 log cfu/g) varied from 7 to 32 and from 49 to 66, ug/g, respectively. No synergistic effect of SDS was observed in the challenge test on meat samples. Any detectable amount of histamine was produced in the meat samples held at melting ice temperature (0-2°C) for 7 days. The effect of NTAP on the quality properties of mackerel’s fillets were negligible, therefore shows potential for control of histamine-producing bacteria and histamine formation, although practical application can be hypothesised only if prolonged storage is foreseen or the catch suffers thermal abuse.